BUDIDAYA CABAI RAWIT SISTEM HIDROPONIK SUBSTRAT DENGAN VARIASI MEDIA DAN NUTRISI - Djoko Purnomo; Dwi Harjoko; Trijono Djoko Sulistyo (Caraka Tani: Journal of Sustainable Agriculture, 2016)
The study aimed to determine which substrate and nutrition that gives the best result in improving growth and yield of Capsicum frutescens. The study design using CRD (completely randomized design) with two factors, namely substrates (6 levels: charcoal husks, fractional tiles, fractional bricks, arenga fiber, beach sand, husk steamed) and nutrition (2 levels: standards, standards with NPK). The study was conducted October 2015 until March 2016 in screen house Faculty of Agriculture, Sebelas Maret University. Data were analyzed using analysis of variance and if significant difference continued with DMRT (Duncan Multiple Range Test) level of 5%. The results showed that the kinds of substrates significantly affect all variables of Capsicum frutescens (plant height, leaf number, branch number, total interest, diameter trunk, root length, root volume, fresh weight of plants, plant dry weight, fruit weight and number of fruit), and the addition of NPK nutrition significantly affect variable leaf number, branch number, and fresh weight of plants.